CONTRIBUTING FACTORS RELATED TO TYPE 2 DIABETES MELLITUS AMONG ELDERLY: RETROSPECTIVE COHORT STUDY IN LAMPUNG-INDONESIA - Setiawati Setiawati; Septina Rahmayati; Marliyana Marliyana (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Type II Diabetes Mellitus is the most common non-communicable diseases among the elderly. Several modifiable and non-modifiable factors contributed to the occurrence of these diseases.Purpose: Describing of the factors related to the occurrence of type 2 Diabetes Mellitus among the elderly at an integrated development post non- communicable diseases (Posbindu PTM Way Halim) Bandar Lampung-Indonesia.Methods: The type of this research is quantitative, from database in the medical record with total of 74 by purposive random sampling. Data analyzed by univariate and bivariate (chi-squared).Results: Smoker (p-value = 0.016; OR 3.429), physical activity (p-value = 0,000 ; OR 7.467) and waist circumference (p-value = 0.011 OR 4,091). Those were main factors that influence to the occurrence of DM among eldely. Conclusion: It is suggested to management Public Health Services (Puskesmas) to establish a more integrated development post non- infectious diseases (Posbindu) to reach all the elderly. By controlling all of the factors that influence the occurrence of type II DM in various ways, so that the elderly will have a better life and prevent the complications